PELAKSANAAN PENINGKATAN KOMPETENSI GURU RUMPUN PENDIDIKAN AGAMA ISLAM (PAI) DI MAN 2 KOTA BENGKULU - Welia Welia (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2020)
Based on the research results, the implementation of the application of the competency of teachers clumpsof PAI in MAN 2 Kota bengkulu in implementation have been met and the components implemented are fulfilled aspedagogical them is to make learning device, the annual program, the program semi-annual, week effective, evaluation,analysis, creation problems, remedial, mastery of teaching materials. Implementation of the application of the professionalcompetence of teachers clumps of PAI in MAN 2 Kota Bengkulu, in the fields of profession that is responsible in carryingout duties as a teacher, to be helping his fellow peers, obey pereturan, discipline, and control of what is in itself accordingto scientific fields respectively, Thus the implementation of pedagogical competence and professional competence ofteachers has been fulfilled.